Pemanfaatan Teknologi Digital dalam Pembelajaran Konstruktivisme: Meningkatkan Kualitas Pendidikan di Era Digital - Azizah Siti Lathifah (Pusat Riset dan Inovasi Nasional, 2024)
Today's technology has had a significant impact in a variety of sectors, including education. Education today is not only done offline in the classroom, but also through interactive and collaborative online classes using a meeting app. The aim of this study is to explore a wide range of digital technologies that can be used in a constructivist-based learning approach to improve the quality of education in the digital age. The main issue in this study is the importance of the use of digital technology in the teaching learning process with a learning approach based on constructivism. The method used in this research is the study of literature or Library reviews, by collecting and analyzing various journals on digital technology, constructivism, and education. The result of this research is that digital technologies integrated into constructivist-based education can help improve the quality and efficiency of education. In conclusion, digital technology has the potential to improve the quality and efficiency of learning constructivism in the digital age, but should be used wisely and responsibly by teachers and pupils.